Gigahertz harmonic mode-locking with multi-watt sub-60-fs pulses in a Mamyshev oscillator - Feihong Qiao; Ze Li; Ning Jia; Xiangtong Zhai; Hao Liang; Zhiguo Lv (High Power Laser Science and Engineering)
The Mamyshev oscillator (MO) is well-known for its high modulation depth, which provides an excellent platform for achieving both high average power and short pulse durations. However, this characteristic typically limits the high-repetition-rate pulse generation. Herein, we construct an MO that achieves a gigahertz (GHz) repetition rate through harmonic mode-locking. The laser can reach up to the 93rd order, which corresponds to the repetition rate of 1.6 GHz. The maximum achieved output average power is 3 W at a repetition rate of 1.2 GHz (69th order), with the corresponding pulse duration compressed to 51 fs. To our knowledge, this is the first time that the GHz repetition rate in an MO has been obtained simultaneously with the recorded average power and pulse duration.